Lactobacillus plantarum ameliorates the immunological impacts of titanium dioxide nanoparticles (rutile) in Oreochromis niloticus. (24th April 2022) - Sherif, Ahmed H.; Khalil, Riad H.; Tanekhy, Mahmoud; Sabry, Nader M.; Harfoush, Mohammed A.; Elnagar, Mahmoud A.
Abstract: Titanium dioxide (TiO2 ) is used in numerous applications, such as medicinal products, cosmetics and food whitening (E171). This work aimed to assess the protective role of Lactobacillus plantarum in the TiO2 nanoparticles induced toxicity in Oreochromis niloticus . A total number of 600 O . niloticus was divided into four groups G1–4; G1 was fed on the basal diet, G2 fed on L . plantarum, G3 fed on contaminated TiO2  NPs‐diet (1 mg/kg body weight), while G4 fed on contaminated TiO2  NPs‐diet then treated with L . plantarum for the same period. Fish immunity was evaluated at 10, 20 and 30 days except G4 were at 20, 40 and 60 days. The gene expression of the interleukin (IL)‐1β, IL‐6, IL‐10 and tumour necrosis factor‐α were significantly enhanced in G4 compared with G3. On days 10 and 20, the phagocytic activity was significantly increased in G4 compared with G1 and G3, while it was decreased on day 30 in G4 and G3. In addition, oxidative burst activity and serum antibacterial activity had the same trend indicating the immunosuppression effects of TiO2  NPs. The mortality rate of fish challenged against Aeromonas hydrophila was decreased in G4 (30%, 50% and 60%) compared with G3 (50%, 50% and 70%) respectively. The antioxidant enzymes catalase, glutathione peroxidase and superoxide dismutase were stimulated, indicating the generation of reactive oxygen species by TiO2 in exposed O . niloticus . It was concluded that L . plantarum could protect O . niloticus against TiO2  NPs‐induced immunosuppression by enhancing their immune response and oxidative status.